Design of Experiment pada proses Immersion Tin Plating - Widya Rika Puspita; Lindawani Siregar; Ika Karlina Laila NS; Ira Zamzami; Budiana Budiana; Fitriyanti Nakul; Nur Sakinah Asaad; Adlian Jefiza (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2022)
PCB (printed circuit board) is a copper-coated board that is a container for electronic components arranged to form electronic circuits. Copper surfaces that are easy to oxidize (corrosion) need to be soothed with a layer of Sn (tin). Based on the TFME study case, the electroplating technique requires more cost for tin plating. The immersion process of the tin plating model is superior in terms of cost and quality. To determine the right combination parameters so as to obtain a thickness that is in accordance with the IPC-4554 standard, namely a minimum of 1000 nm, the research method used is Design of Experiments (DoE). There are nine experimental combinations of the DoE results. Combination parameter testing is done using a SEM (scanning electron microscope) machine. The combination of four to nine has met IPC standards with a thickness of between 1040-1540 nm. The correct parameter is obtained by the combination of 5 with the parameter temperature of 700 and time of 60 minutes, and the result is an average thickness of 1.2 µm and has an uncertain value of the measurement is 7.